Faktor-faktor yang Berperan terhadap Kecemasan pada Mahasiswa Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Sam Ratulangi - Sthevanus N. Moe; Herdy Munayang; Theresia M. D. Kaunang (Medical Scope Journal, 2024)
Abstract: Anxiety is a prevalent issue among medical students due to the demanding schedule, frequent module exams, OSCE, and tutorial activities. This study aimed to determine the relationships between factors contributing to anxiety among students at the medical faculty. This was an analytical observational study with a cross-sectional design, using primary data from questionnaires administered to the students. Respondents were students of third semester Faculty of Medicine of Universitas Sam Ratulangi. The results showed that majority of respondents experienced expected parenting model, first-born, come from outside the region, with severe academic stress, moderate stress in the learning process, moderate interpersonal stress, moderate social stressors, mild pressure from lacking motivation, and moderate stress in group activities. Respondents without anxiety were 41.8% of students, followed by mild anxiety in 28.2%, moderate anxiety in 17.3%, severe anxiety in 9.1%, and very severe anxiety in 3.6%. Factors related to anxiety were academic stressors (p=0.001), learning process stressors (p=0.001), interpersonal stressors (p=0.000), and group activity stressors (p=0.000). In conclusion, academic stressors, learning process stressors, interpersonal stressors, and group activity stressors are related to anxiety among the third-semester medical education students at Unioversitas Sam Ratulangi. Keywords: anxiety; stressor; medical students; academic demands    Abstrak: Kecemasan merupakan permasalahan pada mahasiswa fakultas kedokteran akibat jadwal pembelajaran yang padat, ujian modul yang sering, OSCE serta kegiatan tutorial. Penelitian ini bertujuan untuk mengetahui hubungan faktor-faktor yang berperan terhadap kecemasan pada mahasiswa fakultas kedokteran. Jenis penelitian ialah analitik observasional dengan desain potong lintang menggunakan data primer dari kuesioner kepada mahasiswa. Responden penelitian ialah mahasiswa semester III Fakultas Kedokteran Universitas Sam Ratulangi (FK Unsrat). Hasil penelitian mendapatkan mayoritas responden mendapatkan model pengasuhan yang diharapkan, anak non sulung, perantau, dengan stres akademik berat, stres proses pembelajaran sedang, stres interpersonal sedang, stresor sosial sedang, tekanan dari motivasi yang kurang secara ringan, dan stres aktivitas kelompok sedang. Responden tidak mengalami kecemasan sebanyak 41,8%, disusul oleh  kecemasan ringan sebanyak 28,2%, kecemasan sedang 17,3%, kecemasan berat 9,1%, dan kecemasan sangat berat 3,6%. Faktor-faktor yang memiliki hubungan korelasi dengan kecemasan ialah stresor akademik (p=0,001), stresor pembelajaran (p=0,001), stresor interpersonal ((p=0,000), dan stresor aktivitas berkelompok (p=0,000). Simpulan penelitian ini ialah terdapat hubungan bermakna stresor akademik, stresor pembelajaran, stresor interpersonal, dan stresor aktivitas berkelompok dengan ansietas pada mahasiswa Semester III Fakultas Kedokteran Universitas Sam Ratulangi. Kata kunci: kecemasan; stresor; mahasiswa kedokteran; tuntutan akademik